Responsabilidade socioambiental da indústria têxtil: um estudo sobre a logística reversa na empresa C&A - Pichinin, Antonella Mazzine (2022)
The history of the textile industry has a worldwide relationship with the means of production and the economy. Although technological evolution has made it possible to increase production capacity, with the exchange of manual production for the use of machines, on the other hand, there was a stimulus for the exploitation of natural resources, and the emergence of a lot of waste, as a result of the production process, impacting the environment in different ways. Thus, it was extremely important to create legislation in this sense, enabling the emergence of several good practices, such as reverse logistics. In this line, the work intends to analyze the reverse logistics process in the company C&A, in Brazil in 2021, against the National Solid Waste Policy as a possible solution to minimize the socio-environmental impacts of the textile industry. The work thus seeks to answer the following question: What are the limits and possibilities of implementing the reverse logistics process from the application of the National Solid Waste Policy, in the year 2021, to configure itself as a minimizing factor of the socio-environmental impacts of the textile industry, notably in the company C&A in Brazil? In order to answer this question, the methodology and action strategy to make this research viable follow the four-dimensional Basic Theory, Approach, Procedure and Technique. Regarding the base theory, the systemic-complex approach will be adopted, through the deductive approach, which, starting from theories and laws in a broad premise, foreshadows the realization of particular phenomena in a specific premise, performing a downlink. With regard to the method of procedure, the analysis to be carried out will have as procedures the bibliographic research, the document analysis and the case study. The technique used for the bibliographic research procedure will be the production of annotations and extended abstracts; for document analysis, the technique used will be the creation of tables and graphs; and, finally, for the case study, the analysis of the company's history will be used, its growth in the market, as well as its involvement for the creation of the project and for the implementation of the reverse logistics process, verifying difficulties and benefits. This dissertation was divided into three chapters, the first being responsible for presenting the historical evolution of the world and Brazilian textile industry. The second chapter, in turn, addresses the institutionalization process of the National Solid Waste Policy in Brazil. Finally, the third chapter checks the limits and possibilities of C&A's socio-environmental projects, in the year 2021, especially those involving reverse logistics, with an emphasis on observing the benefits provided and the difficulties of implementing this practice to minimize the impacts of the textile industry on the environment. From this perspective, the answer to the question presented is that reverse logistics is an excellent tool for minimizing environmental impacts, especially in C&A, through the annual sustainability report presented with the 2021 results.